Crisis and disaster management to reduce gas stations in the urban areas in Saudi Arabia - Alghamdi, Abdulrahman Ahmed (Journal of agricultural, environmental and veterinary sciences, 2019)
Research Objectives: In this research، we aim to achieve the following objectives: 1- Identify the risks of gas filling in the urban area in Saudi Arabia. 2- Apply crisis and disaster management to reduce this phenomenon. 3- Safe ways and means to address this problem. 4- Provide suggestions and recommendations that can contribute to limit the risk. Research Questions: 1- What are the risks which could be occurred as a result of gas filling within the urban areas? 2- Are there advanced ways and means to replace or deliver cooking gas to homes? Research Results: The goal of crisis and disaster management is to improve the performance، efficiency and effectiveness in extrapolating the future to the extent that it achieves an integrated understanding of the nature of the crisis or disaster which can achieve rapid and effective response to the rapid changes of crises and disasters through the preparation of pre-plans and readiness to confront them and reduce the damage to ensure the restoration of the situation.